Penerapan Model Pembelajaran Kooperatif Tipe Scramble dalam Meningkatkan Prestasi Belajar IPS Peserta Didik Kelas VIII B SMPK Jos Soedarso Ende - Getrudis Sala (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
This study aims to determine and to describe: (1) The implementation of the Scramble type cooperative learning model in Social studies in Jos Soedarso Ende Junior High School, (2) The learning achievement of Grade VIII students in Social studies subjects at SoedarsoEnde Junior High School after applying the Scramble learning model. This research is a kind of Classroom Action Research (CAR) conducted in 2 cycles. Data collection techniques used are (1) observation, (2) tests and (3) documentation. The subjects of this study were 17 students grade VIII B. The results of improved learning show that; (1) Scramble Type Cooperative learning model has been implemented in social studies learning specifically on Excellence and Limitations Between Space and Its Effect on Economic Activities teaching material in Class VIII students at Jos SoedarsoEnde Junior High School. In the first cycle the application rate was 67% or included in the unfavorable category and increased in the second cycle by 92% or included in the very good category, (2) After applying the scramble learning model, the learning achievements of class VIII B students in cycle I were 4 students who did not complete became 100% complete in cycle II. Thus it can be concluded that the application of the scramble learning model can improve the learning outcomes of grade VIII B students at Jos Soedarso Ende Junior High School